IDENTIFIKASI RESPON PESERTA DIDIK TERHADAP VIDEO PEMBELAJARAN FISIKA BERBASIS STEM PADA MATERI MOMENTUM DAN IMPULS - Darmatiara, Dedek; Pratama, Wahyu Adi; Susbiyanto, Susbiyanto; Chaw-Yangon , Ei Phyu Chaw-Yangon (EduFisika: Jurnal Pendidikan Fisika, 2024)
This study aims to identify students' needs for learning media in the form of physics learning videos that are needed and needed by students, especially on momentum and impulse material. This research is a quantitative study with a sample of class XI students at SMA Negeri 3 Muaro Jambi who have studied the momentum and impulse material and the research population, namely all students at SMA Negeri 3 Muaro Jambi. The research data was obtained from filling out the students' needs questionnaire results sheet for the required learning media. The results of filling out the students' needs questionnaire sheet show that in learning physics they have not used learning media in the teaching and learning process, so that learning is not conveyed in detail, both in terms of material and visualization, and students need learning media that is able to explain learning material in detail, and provide solutions in explaining learning material.